Environmental and Green Orientation as Drivers of Firm Performance: A Natural Resource-Based View Review - Suroto Suroto (Journal of Business, Social and Technology, 2026)
Background: Sustainable development has moved environmental practices from compliance to strategic economic resources. Based on the Natural Resource-Based View (NRBV), this paper conducts a systematic review of the impact of green and environmental orientation upon competitive strategy and firm performance. Objective: This study aims to (1) identify dominant research themes in the green and environmental orientation literature, (2) examine prevailing theoretical and methodological approaches, and (3) develop an integrative NRBV-based strategic framework explaining how sustainability-oriented resources are converted into competitive strategy and superior firm performance. Methods: Following the PRISMA 2020 guidelines, a systematic search of the Scopus database was conducted in January 2025 using terms including "green orientation," "environmental orientation," "competitive strategy," and "firm performance." After screening 104 initially identified articles by title, abstract, and inclusion criteria (peer-reviewed, English-language, Scopus-indexed, published 2018–2025), 60 articles were retained for thematic synthesis. Results: Environmental and green dynamics create value in the economic dimension via innovation, efficiency, and competitive strategy. Purpose: Although competitive strategy and green innovation mediate their effects on firm performance, the literature remains fragmented along theoretical, methodological, and contextual lines. The objective of this review is to (1) clarify mechanisms underlying competitive advantage, (2) develop a NRBV-based framework, and (3) highlight important gaps in research. Conclusion: Green and environmental orientation can enhance firm performance through competitive strategy and innovation, as they can be strategically valuable resources. Future studies that adopt longitudinal and cross-country designs should address existing methodological and contextual gaps.